Administrative dispute and the administrative adjudication process in contemporary serbia -some problems of reform and amendment directions- - Zoran R. Tomić (Zbornik Radova Pravnog Fakulteta u Splitu, 2010)
The subject of this paper is the functioning of one part of the new judicial system in Serbia put in place by judicial law in 2008, and based on the Serbian Constitution of 2006. It deals with the administrative judiciary, i.e. administrative dispute and the administrative adjudication process. It focuses mainly on some legal gaps and insufficiencies of their current and future legal regulation commencing from 1.1.2010. It is already the second half of 2009, and the two fundamental, mostly exceeded regulations, together with their solutions from the area of administrative-procedural law have not been radically amended. This law is derived from the Federal Republic of Yugoslavia from the General Administrative Procedure Act (of 1977 further referred to in the text as “ZUP”) and the Administrative Dispute Act (of 1996 further referred to as “ ZUS”). However, further on, only one issue in administrative dispute and administrative judicial procedure is discussed, mainly de lege ferenda, including some important contentions of an organisational character.